Problems faced by Western expatriate managers in East Europe : evidence among Finnish expatriates in Russia and Estonia - Suutari, Vesa (Nomos, 2017)
A common human resource management strategy among Western companies in international operations is the use of home-country expatriate managers although expatriate adjustment has been found to involve difficulties. In the light of this the present study analyses the issues faced by Finnish expatriate managers working in Russia or Estonia. Three aspects were studied: adaptation to society, adaptation at the work place, and company-level management problems with which expatriates have to deal in their managerial job. The results indicate that various kinds of problems appear in all these areas and that the preparation of both expatriates and companies entering these markets was usually inadequate.

Eine unter westlichen Unternehmen alltägliche Personalmanagementstrategie ist der Einsatz von Managern aus dem Mutterland des Unternehmens, obwohl die Eingliederung von Mitarbeitern anderer Staatsbürgerschaft mit Problemen behaftet ist. Vor diesem Hintergrund analysiert die vorliegende Studie die Schwierigkeiten, denen finnische Manager bei der Arbeit in Rußland oder Estland begegnen. Drei Aspekten wurde dabei besondere Aufmerksamkeit gewidmet: Anpassung an die Gesellschaft, Anpassung an den Arbeitsplatz und Managementprobleme auf der Unternehmensebene; alles Probleme, mit denen ausländische Manager in ihrer Arbeit umgehen müssen. Die Ergebnisse der Studie zeigen, daß in allen diesen Gebieten verschiedenartige Probleme auftreten, und daß sowohl die Vorbereitung der Manager auf ihren Auslandseinsatz als auch die Vorbereitung der Unternehmen, die in diese Märkte eintreten, in der Regel unangemessen war.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|